Revitalization of the Traditional Archery Sport Art of Jemparingan through the Unisma House of Culture and Civilization Program: Revitalisasi Seni Olahraga Panahan Tradisional Jemparingan Melalui Program Rumah Budaya dan Peradaban Unisma - Nirmala Susanti; Dewa Anjar Wahyudi; Nurul Kholifah; Zahrotunnisa Salsabila; Ifit Novita Sari (Universitas Lancang Kuning, 2023)
Students and university students are potential human resources for the future of the nation that must be processed seriously as assets that must be maintained, educated, and developed. The current era of disruption has challenges in the form of a large flow of globalization with accelerated technology and information, students and college students need to increasingly have the power of focus, peace of mind, and mental toughness to achieve high achievement and noble character. One of the efforts that can be made to achieve these competencies is through the practice of traditional archery sport Jemparingan. In addition, the younger generation also strives to preserve the culture of the archipelago. In the current era of globalization, Jemparingan traditional archery has been neglected by the people who own it. Through the Jemparingan Traditional Archery Sport Art Training program in the House of Culture and Civilization of Unisma, the implementation team wants to introduce the local wisdom of the archipelago to the younger generation. This training applies a service learning method that is in accordance with the consideration of field conditions and needs.